2019
DOI: 10.5194/acp-19-3433-2019
|View full text |Cite
|
Sign up to set email alerts
|

What caused the extreme CO concentrations during the 2017 high-pollution episode in India?

Abstract: Abstract. The TROPOspheric Monitoring Instrument (TROPOMI), launched 13 October 2017, has been measuring carbon monoxide (CO) concentrations in the Earth's atmosphere since early November 2017. In the first measurements, TROPOMI was able to measure CO concentrations of the high-pollution event in India of November 2017. In this paper, we studied the extent of the pollution in India, comparing the TROPOMI CO with modeled data from the Weather Research and Forecasting model (WRF) to identify the most important s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…Unlike the surface CO mixing ratios, the majority of the column CO mixing ratio is contributed by the background signal. A recent study conducted by Dekker et al, (2019) concluded that there exists an underestimation in GFAS fire emission data over the Indian region, which is supported by our findings. However, over the Punjab region, biomass burning played a significant role in determining the ground level CO measurements, especially during 6-9 of November, during which enhanced fire activities occurred.…”
Section: Contribution Of Different Sources To the Observed Concentrationsupporting
confidence: 91%
See 4 more Smart Citations
“…Unlike the surface CO mixing ratios, the majority of the column CO mixing ratio is contributed by the background signal. A recent study conducted by Dekker et al, (2019) concluded that there exists an underestimation in GFAS fire emission data over the Indian region, which is supported by our findings. However, over the Punjab region, biomass burning played a significant role in determining the ground level CO measurements, especially during 6-9 of November, during which enhanced fire activities occurred.…”
Section: Contribution Of Different Sources To the Observed Concentrationsupporting
confidence: 91%
“…It achieves higher spatial and temporal (daily) resolution than almost any other inventory and can estimate near-real-time emissions. A number of studies have reported the underestimation of GFAS in fire emissions due to the limitations of the MODIS instruments, which do not capture all of the biomass burning emissions (Cusworth et al, 2018;Dekker et al, 2019;Huijnen et al, 2016;Kaiser et al, 2012;Mota and Wooster, 2018).…”
Section: Wrf-chem-ghg Modelmentioning
confidence: 99%
See 3 more Smart Citations